2014
DOI: 10.1016/j.bbagrm.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin dynamics during spermiogenesis

Abstract: The function of sperm is to safely transport the haploid paternal genome to the egg containing the maternal genome. The subsequent fertilization leads to transmission of a new unique diploid genome to the next generation. Before the sperm can set out on its adventurous journey, remarkable arrangements need to be made during the post-meiotic stages of spermatogenesis. Haploid spermatids undergo extensive morphological changes, including a striking reorganization and compaction of their chromatin. Thereby, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
489
2
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(513 citation statements)
references
References 232 publications
7
489
2
15
Order By: Relevance
“…This finding remains contentious -they themselves found that, despite the reduced chromatin partitioning of MDC1 upon NCL depletion, immunofluorescent localization of MDC1 to DSB foci was unaffected, while Goldstein and colleagues' ChIP-based assay found no reduction in the recruitment of MDC1 to a defined DSB site in the absence of NCL (Goldstein et al 2013). It is known, however, that RNF8/RNF168-dependent H2A/H2B ubiquitination is an important activating step in histone eviction both following DNA damage and during spermiogenesis, in which histone octamers are globally evicted from DNA and replaced by protamines to facilitate greater DNA compaction; such observations suggest that regulation of MDC1 and its partners by NCL could conceivably play a role in NCL's histone-chaperone activity at DSBs (Ikura et al 2007, Lu et al 2010, Rathke et al 2014. Collectively, these data argue for a model in which NCL recruitment to DSBs via the MRN complex facilitates the proximal nucleosome destabilization by chromatin remodeling complexes, possibly through the actions of MDC1 and its targets RNF8/RNF168, and ultimately facilitates NHEJ-and HR-mediated DSB resolution (Goldstein et al 2013).…”
Section: Npm1 and Ncl In Histone Remodeling And Double Strand Break Rmentioning
confidence: 85%
“…This finding remains contentious -they themselves found that, despite the reduced chromatin partitioning of MDC1 upon NCL depletion, immunofluorescent localization of MDC1 to DSB foci was unaffected, while Goldstein and colleagues' ChIP-based assay found no reduction in the recruitment of MDC1 to a defined DSB site in the absence of NCL (Goldstein et al 2013). It is known, however, that RNF8/RNF168-dependent H2A/H2B ubiquitination is an important activating step in histone eviction both following DNA damage and during spermiogenesis, in which histone octamers are globally evicted from DNA and replaced by protamines to facilitate greater DNA compaction; such observations suggest that regulation of MDC1 and its partners by NCL could conceivably play a role in NCL's histone-chaperone activity at DSBs (Ikura et al 2007, Lu et al 2010, Rathke et al 2014. Collectively, these data argue for a model in which NCL recruitment to DSBs via the MRN complex facilitates the proximal nucleosome destabilization by chromatin remodeling complexes, possibly through the actions of MDC1 and its targets RNF8/RNF168, and ultimately facilitates NHEJ-and HR-mediated DSB resolution (Goldstein et al 2013).…”
Section: Npm1 and Ncl In Histone Remodeling And Double Strand Break Rmentioning
confidence: 85%
“…We isolated dlp 45 , an allele carrying a 5-bp insertion (TCGTA), as evidenced by PCR analyses, causing a frameshift in the open reading frame (ORF) and introducing a new stop codon. dlp 45 is predicted to encode a truncated protein of 869 amino acids, lacking the C-terminal DHR. However, the homozygous dlp 45 allele is both viable and fertile.…”
Section: Resultsmentioning
confidence: 99%
“…Male germ cells undergo stem cell self-renewal, mitotic divisions in spermatogonial proliferation, genomic rearrangement by meiotic homologous recombination at the spermatocyte stage, and morphological changes of round spermatids into elongated spermatids to form mature spermatozoa (1)(2)(3). During spermiogenesis, nucleosomal histone proteins are replaced with transition nuclear proteins (TNPs) and subsequently, protamines, the major nucleosomal proteins in spermatozoa.…”
mentioning
confidence: 99%
“…During spermiogenesis, nucleosomal histone proteins are replaced with transition nuclear proteins (TNPs) and subsequently, protamines, the major nucleosomal proteins in spermatozoa. Moreover, epigenetic modifications, such as histone methylation, dramatically change throughout spermatogenesis (3,4).…”
mentioning
confidence: 99%